EVALUASI RESPON STRUKTUR AKIBAT PENAMBAHAN LANTAI DENGAN METODE ANALISIS STATIK DAN DINAMIK RESPONSE SPECTRUM ( STUDI KASUS : PEMBANGUNAN GEDUNG FAKULTAS KEDOKTERAN UIGM ) - Imaduddin, M.; Melani, Septa; Oemiati, Nurnilam; Setiawati, Mira (Bearing : Jurnal Penelitian dan Kajian Teknik Sipil, 2024)
In 2022, Indo Global Mandiri University (UIGM) will construct the Faculty of Medicine building. In the initial planning of the development project, the construction of a 6-storey building was carried out, but after the implementation process was carried out, 5 floors were proposed to add floors, where initially the building only had 6 floors, it was made into a 7-storey building.The purpose of this research is to determine the structural behavior of the UIGM Palembang medical faculty building due to the addition of floors, whether the building meets the safety requirements in accordance with the Indonesian National Standard (SNI) reference for planning the latest earthquake resistance due to the addition of an earthquake, which in this study used software assistance ETABS and Response Spectrum analysis.Results of evaluation of structural behavior due to the addition of floors with a building height of 32.5 m in safe conditions as required by SNI 1726-2019 All deviations between floors are said to be okay, which means the UIGM Faculty of Medicine Building has met safety requirements according to the Indonesian National Standard (SNI) reference . The P-Delta value for the 7-storey building in the x and y directions still meets the requirements of SNI 1726:2019, which is still below the P-Delta limit. The addition of a floor to the UIGM Faculty of Medicine Building is categorized as safe because the behavior of the building structure does not indicate an unsafe condition (Not OK)